PHENOMENOLOGICAL REFLECTIONS ON POWER AND VULNERABILITY IN CYBERSPACE BY FILIPINO YOUTH: Implications to Church in Dialogue with Digital Culture - Peracullo, Jeane C (Asian Horizons, 2013)
This article focuses on selected students’ reflections in Philosophy and Gender courses at De La Salle University in the Philippines. These musings are about their engagement of, with, and in cyberspace particularly through virtual games and social networks using a philosophical method known as Phenomenology. Through phenomenology, students critically examined their own experience as they navigated cyberspace and how such experiences impacted on the way they have understood themselves, their gender identities, and even sexual orientation. The activity enabled them to reflect deeply into their own engagement and whether such made them empowered or vulnerable. These engagements by young people are a special import to the Church which is highlighted by Pope Benedict XVI in his 47th World Day of Communications Message (2013)1 where he acknowledges that the “development of digital social networks which are helping to create a new “agora”, an open public square in which people share ideas, information and opinions, and in which new relationships and forms of community can come into being.”